State writing, subversion and citizenship in Southern Rhodesia’s state of emergency, 1959–1960 - Alexander, JH (Routledge, 2019)
This article takes a moment of political upheaval – Southern Rhodesia’s 1959 State of Emergency – to explore the uses of writing in the remaking of state authority and citizenship. The 1950s had produced a powerful bureaucratic state, a shaky attempt at multi-racial “partnership,” and African aspirations to a citizenship able to encompass equality, rights and self-determination. The Emergency brought the tensions in these modes of government and citizenship to the fore. The article explores the working out of these tensions in two instances: the bureaucratic attempt to manage political detainees, and the police evidence used to substantiate charges of subversion on the part of nationalists in court. The article traces the limits of the state’s “lawfare” and the means by which detainees and nationalists developed new understandings of citizenship as aspirational imaginary, legal condition and practical tool, through the written word.